Uses of Energy Psychology Following Catastrophic Events - Feinstein, David (Frontiers in Psychology, 2022)
Energy psychology, as most widely practiced, integrates the manual stimulation of acupuncture points with imaginal exposure, cognitive restructuring, and other established psychotherapeutic procedures. Efficacy for energy psychology protocols has been established in more than 120 clinical trials, with meta-analyses showing strong effect sizes for PTSD, anxiety, and depression. The approach has been applied in the wake of natural and human-made disasters in more than 30 countries. Four tiers of energy psychology interventions following the establishment of safety, trust, and rapport are described, including 1) immediate relief/stabilization, 2) reducing limbic arousal to trauma-based triggers, 3) overcoming complex psychological problems, and 4) promoting optimal functioning. The first tier is most pertinent in psychological first aid immediately following a disaster, with the subsequent tiers progressively being introduced over time with complex stress reactions and chronic disorders. Advantages of adding the stimulation of acupuncture points to a conventional exposure approach are identified, and challenges around cultural sensitivities and unintended effects are discussed. After establishing a framework for introducing energy psychology in disaster relief efforts, reports from a sampling of settings are presented, based on interviews with this paper’s author. These include accounts of relief work with survivors of mass shootings, genocide, ethnic warfare, earthquakes, hurricanes, tornadoes, floods, wildfires, and the COVID-19 pandemic. Hundreds of other reports from the field show a pattern of strong outcomes following the use of energy psychology both immediately following disasters and in the subsequent treatment of trauma-based psychological difficulties. Many of these accounts corroborate one another in terms of rapid relief and long-term benefits. Finally, examples of more efficient delivery methods utilizing large groups, lay counselors, digital technology, and cultivating community resilience are presented.